UP-BCO Vendor Operations Improvement Project - Antigua, Bryan Lee (Technology Management Center, 2012)
Assessment and improvement of food cart design in terms of Quality, Operation and Service Efficiency, and Food Safety for the Samahan ng Manininda sa UP Campus, Inc. and UP Business Concessionaires Office.